2006
DOI: 10.3122/jabfm.19.6.548
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Race and Gender on Family Physicians' Annual Incomes

Abstract: Purpose: Specialty, work effort, and gender have been shown to be associated with physicians' annual incomes. We hypothesized that provider race might also be associated with differences in family physicians' incomes. Therefore, we conducted a study that used survey data to explore the relationship between provider gender and race and family physicians' annual incomes.Methods: We used survey responses collected by the American Medical Association (AMA) throughout the 1990s from 786 white male, 20 black male, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
23
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 31 publications
5
23
2
Order By: Relevance
“…This result was similar to the general family physician population, as demonstrated by Weeks and Wallace in 2006, where they corrected for work effort, provider characteristics, and practice characteristics 15. In the current study, the odds of a male physician being a high income earner were 6.6 times higher than those of a female physician.…”
Section: Discussionsupporting
confidence: 88%
“…This result was similar to the general family physician population, as demonstrated by Weeks and Wallace in 2006, where they corrected for work effort, provider characteristics, and practice characteristics 15. In the current study, the odds of a male physician being a high income earner were 6.6 times higher than those of a female physician.…”
Section: Discussionsupporting
confidence: 88%
“… Summary of Included Studies [ [1] , [2] , [8] , [14] , [17] - [32] , [34] - [40] , [43] , [46] - [51] ]. …”
Section: Supplementary Materialsmentioning
confidence: 99%
“…A recent study challenged the assertion that physicians who practice in rural settings are poorly compensated when compared to their urban counterparts: while rural primary care physicians had lower unadjusted incomes than their urban counterparts, after adjustment for lower costs of living and practicing in rural settings, the study found that rural primary care physicians' incomes were 10%‐13% higher than those of their urban counterparts 18 . However, that study used only a single year's data from the Center for Studying Health System Change's Community Tracking Study Physician Survey 19 and did not adjust for a number of important variables including race, the inverted U lifetime earnings pattern that is typical for physicians, and the US Census region practice location that we have previously shown to be associated with the annual incomes of general internists 20 and family physicians 21 …”
mentioning
confidence: 99%
“…Because board certification is associated with higher physician incomes, 41 we included board certification status as an independent variable in the analysis. Finally, because race, 20,21 gender, 20,21,35 and international medical school graduate status 31 have been associated with work effort, practice characteristics, and incomes of primary care physicians, we included those factors in our analysis. Practice characteristics . Physician incomes vary according to US Census region of practice location 33 ; therefore, information on the US Census region, in which the practice was located, was collected.…”
mentioning
confidence: 99%